Palmitate‐mediated induction of neuropeptide Y expression occurs through intracellular metabolites and not direct exposure to proinflammatory cytokines. Issue 3 (20th September 2021) - Tran, Andy; He, Wenyuan; Chen, Jim T. C.; Wellhauser, Leigh; Hopperton, Kathyrn E.; Bazinet, Richard P.; Belsham, Denise D.
Abstract: A contributing factor to the development of obesity is the consumption of a diet high in saturated fatty acids, such as palmitate. These fats induce hypothalamic neuroinflammation, which dysregulates neuronal function and induces orexigenic neuropeptide Y ( Npy ) to promote food intake. An inflammatory cytokine array identified multiple candidates that could mediate palmitate‐induced up‐regulation of Npy mRNA levels. Of these, visfatin or nicotinamide phosphoribosyltransferase (NAMPT), macrophage migratory inhibitory factor (MIF), and IL‐17F were chosen for further study. Direct treatment of the neuropeptide Y/agouti‐related peptide (NPY/AgRP)‐expressing mHypoE‐46 neuronal cell line with the aforementioned cytokines demonstrated that visfatin could directly induce Npy mRNA expression. Preventing the intracellular metabolism of palmitate through long‐chain acyl‐CoA synthetase (ACSL) inhibition was sufficient to block the palmitate‐mediated increase in Npy gene expression. Furthermore, thin‐layer chromatography revealed that in neurons, palmitate is readily incorporated into ceramides and defined species of phospholipids. Exogenous C16 ceramide, dipalmitoyl‐phosphatidylcholine, and dipalmitoyl‐phosphatidylethanolamine were sufficient to significantly induce Npy expression. This study suggests that the intracellular metabolism of palmitate and elevation of metabolites, including ceramide and phospholipids, are responsible for the palmitate‐mediated induction of the potent orexigen Npy . Furthermore, this suggests that the regulation of Npy expression is less reliant on inflammatory cytokines per se than palmitate metabolites in a model of NPY/AgRP neurons. These lipid species likely induce detrimental downstream cellular signaling events ultimately causing an increase in feeding, resulting in an overweight phenotype and/or obesity. Abstract : A model of NPY neurons from the hypothalamus was used to determine the molecular events involved in the palmitate‐mediated induction of NPY and proinflammatory cytokine expression. Palmitate metabolites can induce Npy expression, as well as cytokines, which in turn induce neuroinflammation. The individual subset of cytokines induced by palmitate, as determined by array analysis, do not directly induce Npy expression alone nor does co‐culture with conditioned medium. These finding indicate that these two effects are not interrelated and the regulation of Npy gene expression is dependent upon the intracellular metabolism of palmitate to specific lipids, including ceramide and phospholipids.